Single nucleotide polymorphisms of XRCC3 gene in hepatocellular carcinoma – relationship with clinicopathological features - Avadanei, Elena-Roxana; Giusca, Simona-Eliza; Negura, Lucian; Caruntu, Irina-Draga (Polish Journal of Pathology, 2018)
Recent studies support the involvement of XRCC3 gene polymorphisms in carcinogenesis. Our study focuses on the identification of polymorphic variants of XRCC3 in hepatocellular carcinoma (HCC) and an analysis of the relationship between these polymorphic variants and clinicopathological (including the genotype specific risk) and survival characteristics. Fifty cases of HCC were genotyped using molecular biology techniques for Thr241Met, rs861539 (c.722C>T) and 5’-UTR, rs1799796 (c.562-14A>G) polymorphisms. Statistical analysis was based on 2, Fisher’s, logistic regression (odd ratio – OR), and log-rank tests. Statistically significant differences were shown only for rs1799796 A>G and tumour grade, between wild type (AA) and heterozygote (AG) genotypes, and wild type (AA) and heterozygote & homozygote (AG & GG) genotypes. The logistic regression analysis found an OR of rs1799796 polymorphism occurrence in HCC related to tumour grade. The statistical analysis revealed, for the rs861539 C>T polymorphism, a better survival only for the homozygote genotype (TT) compared to the heterozygote (CT), and for rs1799796 A>G polymorphism, a longer survival for the wild type (AA) compared to heterozygote (AG) and to heterozygote & homozygote (AG & GG) genotypes, respectively. Our results suggest that XRCC3 gene SNPs could influence the tumour aggressiveness expressed by tumour grade.